Juridical Review Of The Executorial Strength Of Liability Certificates In Overcoming Non-Loading Loans (Study At Bank Danamon Cab. Sukaramai Assistant) - Deri Fachrizal (Institute Of computer Science (IOCS), 2021)
The increase in development activities has resulted in an increasing need for the availability of funds, most of which are obtained through credit activities. So it can be said that credit is one of the most important sources of development financing. Credit in banking activities is the most important business activity, because the largest income from bank business comes from income from credit business activities in the form of interest and fees. The problem in this research is how is the procedure for binding the mortgage certificate as collateral for the credit agreement at PT. Bank Danamon Sub-Branch Sukaramai Medan. What are the obstacles to Mortgage in Fulfilling the Rights of the Parties in the Mortgage Execution Process at PT. Bank Danamon Sukaramai Medan Sub-Branch and How the Executional Strength of Mortgage Certificate at PT. Bank Danamon Sub-Branch Sukaramai Medan?. The method used in this research is empirical juridical, namely an approach from the point of view of the rules and implementation of regulations that apply in society, which is carried out by researching secondary data first, then continued by conducting research on primary data in the field. The procedures that must be fulfilled by the customer from the time the credit application is submitted until the payment of a loan granted by the Bank is: Credit Application, Credit Investigation and Analysis, Types of Credit. The importance of binding debt guarantees is so that we can anticipate exactly whether the guarantee will be able to be executed or easily executed. This is because the different procedures for binding guarantees have a direct correlation with how they are executed. Obstacles in the Execution of Mortgage as collateral for credit for legal protection for the interests of Creditors. There are several factors that become obstacles that often occur, namely the resistance by the Mortgage holder himself to the execution of the first Mortgage holder's application. This issue is not regulated in UUHT but is in the Material of Civil Procedure Law. The Mortgage Law has given great executorial power to the Mortgage Certificate, namely by the inclusion of an Irah-Irah which reads